Aturan Kampanye Bagi Aparatur Sipil Negara Sebagai Wujud Asas Netralitas - Ulfa Septian Dika (Faculty of Law, Universitas Airlangga, 2022)
AbstractState Civil Apparatus is a profession for Civil Servants and Government Employees with Work Agreements that work in government institutes. State Civil Apparatus is the servant of the state and a public servant who is required to uphold the ideology of Pancasila, the faithful and defend the Constitution of the Republic of Indonesia in 1945 and the legitimate government, as well as to serve the country and people of Indonesia. The smoothness in the implementation of the task of the government and national development is very dependent on the State Civil Apparatus. So, no wonder if the State Civil Apparatus are required to maintain professionalism and its neutrality, especially when General Elections and Local Elections are taking place. Because not infrequently the State Civil Apparatus who commits a breach of neutrality by participating in campaign activities ahead of the General Election and Local Elections. This Legal research is using 3 (three) approach, namely, the Statute Approach, the Historical Approach, and the Conceptual Approach which in this case is made to answer ratio legis of the prohibition of the participation of the State Civil Apparatus in campaign activities. Keywords: State Civil Apparatus; Prefessional; Neutrality; Campaign; General Elections; Local Elections. AbstrakAparatur Sipil Negara (ASN) adalah profesi bagi Pegawai Negeri Sipil dan Pegawai Pemerintah dengan Perjanjian Kerja yang bekerja pada instansi pemerintah. ASN merupakan abdi negara dan abdi masyarakat yang dituntut untuk memegang teguh ideologi Pancasila, setia dan mempertahankan UUD NRI Tahun 1945 dan pemerintahan yang sah, serta mengabdi kepada negara dan rakyat Indonesia. Kelancaran dalam penyelenggaraan tugas pemerintah dan pembangunan nasional sangat bergantung pada ASN. Sehingga tidak heran apabila ASN dituntut untuk menjaga profesionalitas dan netralitasnya, terutama saat Pemilihan Umum dan Pemilihan Kepala Daerah sedang berlangsung. Karena tak jarang ASN yang melakukan pelanggaran netralitas dengan ikut serta dalam kegiatan kampanye menjelang Pemilihan Umum dan Pemilihan Kepala Daerah. Penelitian hukum ini menggunakan 3 (tiga) pendekatan yaitu, Pendekatan Peraturan Perundang-undangan, Pendekatan Historis, dan Pendekatan Konseptual yang dalam hal ini dilakukan untuk menjawab ratio legis pelarangan kampanye bagi ASN.Kata Kunci: Aparatur Sipil Negara; Profesionalitas; Netralitas; Kampanye; Pemilihan Umum; Pemilihan Kepala Daerah.